Quality of Reported Earnings: An Empirical Study of Indian Banking Industry. Issue 2 (June 2021) - Mangala, Deepa; Singla, Neha
Earnings management (EM) practices by bank managers can prove to be very precarious in smooth running of the financial system of a country. The failure of financial system shocks the entire economy. The present paper aims to assess the quality of earnings in the Indian banking industry. EM is estimated by employing a bank-specific model that measures EM through loan loss provision (LLP) and realized security gains and losses (RSGL). The findings exhibit that public banks practice income increasing and private banks practice income decreasing EM, whereas, combined result reinforces the practice of income decreasing EM. The results indicate that public sector banks use both LLP and RSGL to manage earnings whereas private sector banks increasingly rely on RSGL. Further, direction of EM is gauged by classifying EM on the basis of quartiles. This study has implication for regulators, investor and depositors. Regulators should be stricter regarding policies of LLP. Apart from earnings, investor and depositors should be considered other measures of stability of banks like capital adequacy ratio because earnings may be manipulated.